Effect of Oral intake of Stevia Leaf Powder on Body Weight – An Experimental study - Amna Faruqi; Sikander Subuctageen; Irfan Afzal Mughal; Shahida Parveen; Tooba Zafar; Asma Irfan (Journal of Rawalpindi Medical College)
Introduction: